Efficient cooling system for an indirectly coupled CPV‐CTE hybrid system. (29th June 2021) - Hajji, Mohammed; Labrim, Hicham; Benaissa, Mohammed; Faddouli, Ali; Hartiti, Bouchaib; Ez‐Zahraouy, Hamid
Summary: Nowadays, the hybrid system's coupling of concentrated photovoltaic (CPV) and concentrated thermoelectric (CTE) devices is among the most competitive solutions for exploiting the maximum solar radiation. In this paper, a new concept of this hybrid system integrating a cooling system is investigated for the first time. In particular, the impact of such cooling on the global efficiency of this hybrid system is studied. The effect of the static and dynamic cooling system is evaluated, in which the water and nanofluid based on Cu, Al, and Fe nanoparticles is used for perform cooling, to produce the maximum electricity. A detailed analysis using state‐of‐the‐art thermal transfer calculations and the standard Matlab/Simulink Package has demonstrated that cooling of solar cells is crucial to optimize the CPV system efficiency. Our major finding showed significant superiority of the cooling system‐based nanofluid compared to water. Indeed, at a concentration equal to 10, the gain of the CPV system efficiency under cooling is 5.68% and 2% by Cu and Al nanoparticle‐based nanofluid, respectively, while the water‐cooling is inferior, and the exergy efficiency of the CPV‐CTE can be enhanced to 19% under cooling compared to the efficiency without cooling which is equal to zero. In addition, the cooling system in our model has an interesting advantage that the hot outgoing fluid resulting from the cooling process of the CPV will react as a heat source for CTE during the night to generate the energy without affecting the stored reserve of electricity during the day. Consequently, extending the autonomy of this hybrid system coupling CPV and the CTE to generate energy. Highlights: A new hybrid system CPV‐CTE integrating a cooling system is investigated for the first time. The effect of static and dynamic cooling systems by the fluid and nanofluid is evaluated. The state‐of‐the‐art thermal transfer calculations and numerical method is used. The heat transfer is modeled in a hybrid system under cooling.